The Dynamics of Competition: Phasing of Domestic and External Liberalisation in India - Planning Commission (Planning Commission Government of India, 2006)
Arvind Virmani’s study on the dynamics of competition in India provides a comprehensive analysis of the country’s economic evolution from 1947 to the early 2000s, focusing on the interplay between domestic and external liberalisation and its impact on growth and poverty reduction. The paper contrasts two policy regimes: the Indian Version of Socialism (1950-1980), characterized by import substitution industrialization, extensive state control, and slow growth, and the Experiments in Market Reform (1980 onwards), which introduced market-oriented policies, increased competition, and accelerated GDP growth from 3.5% to 5.8% per annum. Empirical findings highlight the crucial role of total factor productivity, capital deepening, machinery investment, and foreign direct investment in enhancing economic efficiency. Virmani emphasizes the transition from a controlled economy to a market-oriented system, noting the importance of policy coherence, institutional integrity, and liberalisation in stimulating competitiveness, innovation, and sustainable growth. The study underscores that structural reforms and strategic opening of domestic and external markets were central to poverty alleviation and long-term economic resilience, offering valuable insights for policymakers on fostering dynamic efficiency in India’s development trajectory.
Planning Commission Government of India September, 2006
Keywords: India; Economic Liberalisation; Domestic Reforms; External Trade; Total Factor Productivity; Capital Deepening; GDP Growth; Poverty Alleviation; Import Substitution; Market Reforms; Competitiveness; Structural Reforms